Perspectives and Preferences of Preschoolers and Their Parents Regarding Dentist's Attire and Gender - Simin Z. Mohebbi; Samaneh Razeghi; Farin Mizanian; Mohammad Javad Kharazifard (Tehran University of Medical Sciences, 2022)
Objectives: For decades, the white coat has been the uniform of medical professionals. Recently, medical professionals show interest to use alternatives. We aimed to evaluate the perspectives and preferences of children and their parents regarding dentists' attire and gender. Materials and Methods: This cross-sectional study was performed on 4-to 6-year-olds and their parents referred to dental clinics of Tehran School of Dentistry in 2018. Parents completed a questionnaire on demographics and dental fear, and both parents and children were asked about their preferences regarding the gender of dentist and the color of the dentist's attire. Statistical analysis was performed by the logistic regression model. Results: Totally, 148 children (mean age of 5.42±0.71 years, 48% girls) and their parents participated in the study. Most of the participants (81.2% of the children and 68.0% of the parents) preferred colored coats compared with white coat. More than half of the parents preferred a female dentist for their children (56.5%) while most children preferred a male dentist (54.8%). Boys preferred a male dentist as well (P=0.01). The children were reluctant to go for a dental visit and preferred to be visited by a dentist of the same gender as themselves (P=0.041). Conclusion: Wearing colored coats by dentists and giving a chance to choose the gender of dentist in polyclinics may increase the children's cooperation in pediatric settings. Keywords: